The Effectiveness Of Blended Learning Model Towards Learning Outcomes Of Students' Multiplication Operations With Autism - Sukinah Sukinah; Ari Anggit Triadi (Journal of ICSAR, 2022)
This study aims to test the effectiveness of the blended learning model on the learning outcomes of multiplication operations of students with autism in class VII SMPLB at the Pembina State Special School of East Kalimantan Province. This study uses a quantitative approach with the type of Single Subject Research (SSR). The research design uses A-B-A'. The research subjects were three students with autism class VII SMPLB. Data collection techniques using tests and observations. Data is presented in tables and graphs. The data analysis technique uses analysis under conditions and between conditions. The results showed an increase in the acquisition of test scores. The first subject got 40 percent at baseline 1 to 70 percent at baseline 2. The second subject got 30 percent at baseline 1 to 50 percent at baseline 2 The third subject got 30 percent at baseline 1 to 60 percent at baseline 2. Based on these findings, it can be concluded that the blended learning model is effective on learning outcomes of multiplication operations of students with autism. This conclusion is based on increasing scores of all three subjects and is supported by a low percentage of overlap.